2017
DOI: 10.1155/2017/3143642
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Mortar Made with Fine Glass Powdered Particles

Abstract: Different studies investigate the use of waste glass in Portland cement compounds, either as aggregates or as supplementary cementitious materials. Nevertheless, it seems that there is no consensus about the influence of particle color and size on the behavior of the compounds. This study addresses the influence of cement replacement by 10 and 20% of the colorless and amber soda-lime glass particles sized around 9.5 m on the performance of Portland cement mortars. Results revealed that the partial replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 55 publications
2
15
0
1
Order By: Relevance
“…(Matos et al, 2016) reported about 160% higher resistivity (unit kΩ.cm) when fine sand was replaced with 50% glass powder at 86 days. Similar behaviour was also noticed when cement was replaced by 10-20% with glass powder in concrete (Sales et al, 2017). Sulfate resistance of concrete also improved when LCD glass sand was used in concrete and it was improved with the extension of the curing age.…”
Section: Other Durability Propertiessupporting
confidence: 70%
See 2 more Smart Citations
“…(Matos et al, 2016) reported about 160% higher resistivity (unit kΩ.cm) when fine sand was replaced with 50% glass powder at 86 days. Similar behaviour was also noticed when cement was replaced by 10-20% with glass powder in concrete (Sales et al, 2017). Sulfate resistance of concrete also improved when LCD glass sand was used in concrete and it was improved with the extension of the curing age.…”
Section: Other Durability Propertiessupporting
confidence: 70%
“…Therefore, resistance of concrete to carbonation and ingress of oxygen is an important durability parameter. (Sales et al, 2017) studied the influence of various types of glass powder as binder on concrete carbonation and oxygen permeability, as shown in Figure 16. For the carbonation test, after 28 days of water curing, specimens were kept in carbonation chamber for 60 days at an atmosphere of 5% CO2, 48% relative humidity and a temperature of 27.5 ± 2 ∘ C. Carbonation depth increased with increasing glass powder content regardless of the glass type (see Fig 17a).…”
Section: Carbonation and Oxygen Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies into the behavior of the properties of recycled mortars that incorporate recycled glass aggregate (RGA) to replace the usual aggregate (UA) have dealt with different areas, such as the effect of the quantity of replacements (substitution percentages of UA by RGA) [7,8,15], the variations attributable to the color of the glass [10,16], the effect of the RGA particle size [17][18][19][20], and the side effects caused by the type of RGA and its previous use (e.g., proceeding from glass bottles and cathode ray tubes) [15,21]. Similarly, there are also precedents in the use of glass with dust-sized particles as a cement substitute, which has permitted more studies to be included, such as the pozzolanic properties that they provide [1,22,23] and the effect of the size of the dust particles themselves [9,24].…”
Section: Introductionmentioning
confidence: 99%
“…The fibers contribute to a greater toughness to tensile strength and to a reduction of the porosity and of the shrinkage cracks of concrete. Glass recycling is an environmental issue due to its high volume, the excessive cost of recycling it and its insolubility in the environment (Sales et al, 2017). There are many studies on the use of glass waste, such as: in cement mortars applied as pozzolan (Chen et al, 2002) and aggregate applied in concrete (Shayan & Xu, 2006).…”
Section: Introductionmentioning
confidence: 99%